2013
DOI: 10.7454/mssh.v17i2.2961
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompleksitas Tugas, Tekanan Waktu, dan Sifat Kepribadian pada Kinerja

Abstract: AbstrakPenelitian ini bertujuan untuk menguji pengaruh kompleksitas tugas, tekanan waktu, dan lima sifat kepribadian yaitu openness to experience, conscientiousness, extraversion, agreeableness, dan neuroticism pada kinerja auditor. Studi mengenai pengaruh kompleksitas tugas dan tekanan waktu pada kinerja auditor telah banyak dilakukan namun masih menunjukkan hasil-hasil yang tidak konsisten. Oleh karena itu, penelitian ini mencoba memberikan titik pandang baru dengan memasukkan sifat kepribadian auditor, yang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 25 publications
3
21
0
3
Order By: Relevance
“…21,22 Individuals with the agreeableness personality type (agreement) may work together in a team and be trustworthy, caring, kind, helpful, unselfish, and forgiving and do not like to quarrel with others. The study by Barrick et al in Rustiarini,23 showed that this personality has a strong effect on a person's performance. However, the tendency of the individuals with this personality type to create a conducive working environment, avoid conflicts with colleagues, and reduce the chances of conflict at the workplace can in fact cause these conditions that are not favorable for them as it can reduce the enthusiasm in competing for success and achieving higher performance than the achievements of other colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Individuals with the agreeableness personality type (agreement) may work together in a team and be trustworthy, caring, kind, helpful, unselfish, and forgiving and do not like to quarrel with others. The study by Barrick et al in Rustiarini,23 showed that this personality has a strong effect on a person's performance. However, the tendency of the individuals with this personality type to create a conducive working environment, avoid conflicts with colleagues, and reduce the chances of conflict at the workplace can in fact cause these conditions that are not favorable for them as it can reduce the enthusiasm in competing for success and achieving higher performance than the achievements of other colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…The leaders with conscientiousness personality characteristic or "C" personality is the figure of hardworking, disciplined, reliable, organized, meticulous and detailed, and tending to be diligent (Rustiarini, 2013). A person with this personality characteristic has a strong motivation to achieve success (Zimmerman, 2008), and has a task-oriented behavior (Ashton & Lee, 2007), McGregor (1954) calls this as the Y theory.…”
Section: International Conference On Innovation In Engineering and Vomentioning
confidence: 99%
“…An extraversion personality or the "E" personality characteristic highly tends to be talkative, energetic, enthusiastic, assertive and sure, friendly, and sociable (Rustiarini, 2013). Leaders with extraversion characteristic shows a tendency to spend a lot of time in social situations and expresses positive emotions (Judge et al, 2002), he or she is a jaunty and creator of the atmosphere.…”
Section: International Conference On Innovation In Engineering and Vomentioning
confidence: 99%
See 2 more Smart Citations